The Implementation of Policy on Top Leader Position Fulfillment in Bureaucracy Environment Based on State Civil Apparatus Law (The Study in Mataram City Government, Nusa Tenggara Barat Province) - Khairy Juanda; Agus Suryono; Abdul Hakim; Andy Fefta Wijaya (Wacana Journal of Social and Humanity Studies, 2020)
The flow of public tasks of the government in national development is really influenced by the perfect service and the work of government bureaucracy which are parts of the government apparatus that are aimed to provide best service, being balance, and publicly serve the society. This research focuses on the policy of fulfilling the high level position in bureaucracy, by the study in Mataram city government, NTB province.Â  The data analysis technique is interactive model qualitative that was proposed by Miles and Huberman. The result of the study showed that â€œImplementation of development policy and carrier development of Civil Servant have not implement ASN (Civil Servant Apparatus) Law but it still uses old law which influence the obstruction of civil servant (PNS) carrier development.